2016
DOI: 10.3390/molecules21101307
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Analysis of Flavonoids and Phenolic Acids in Snow Chrysanthemum (Coreopsis tinctoria Nutt.) by HPLC-DAD and UPLC-ESI-QTOF-MS

Abstract: A simple, accurate and reliable high performance liquid chromatography coupled with photodiode array detection (HPLC-DAD) method was developed and then successfully applied for simultaneous quantitative analysis of eight compounds, including chlorogenic acid (1), (R/S)-flavanomarein (2), butin-7-O-β-D-glucopyranoside (3), isookanin (4), taxifolin (5), 5,7,3 ,5 -tetrahydroxyflavanone-7-O-β-D-glucopyranoside (6), marein (7) and okanin (8), in 23 batches of snow chrysanthemum of different seed provenance and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 20 publications
2
62
0
Order By: Relevance
“…Peaks 18d, 20d, and 21d showed similar spectra shapes as the previous ones with λ max around 370-380 nm, and a common MS 2 product ion at m/z at 271 that matched the chalcone butein. The pseudomolecular ion ([M-H] − at m/z 433) of peak 18d was coherent with butein hexosides, being the first of them (the majority one) assigned as coreopsin (butein-4′-glucoside), described as a main flavonoid in other species of the Asteraceae family, such as Coreopsis tinctoria (Chen et al, 2016a;Yang et al, 2016). Peak 20d, possessing a molecular weight 42 u higher that peak 18d, was tentatively assigned as acetylcoreopsin, also reported in Coreopsis tinctoria (Yang et al, 2016).…”
Section: Tcsp Pires Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Peaks 18d, 20d, and 21d showed similar spectra shapes as the previous ones with λ max around 370-380 nm, and a common MS 2 product ion at m/z at 271 that matched the chalcone butein. The pseudomolecular ion ([M-H] − at m/z 433) of peak 18d was coherent with butein hexosides, being the first of them (the majority one) assigned as coreopsin (butein-4′-glucoside), described as a main flavonoid in other species of the Asteraceae family, such as Coreopsis tinctoria (Chen et al, 2016a;Yang et al, 2016). Peak 20d, possessing a molecular weight 42 u higher that peak 18d, was tentatively assigned as acetylcoreopsin, also reported in Coreopsis tinctoria (Yang et al, 2016).…”
Section: Tcsp Pires Et Almentioning
confidence: 99%
“…The pseudomolecular ion ([M-H] − at m/z 433) of peak 18d was coherent with butein hexosides, being the first of them (the majority one) assigned as coreopsin (butein-4′-glucoside), described as a main flavonoid in other species of the Asteraceae family, such as Coreopsis tinctoria (Chen et al, 2016a;Yang et al, 2016). Peak 20d, possessing a molecular weight 42 u higher that peak 18d, was tentatively assigned as acetylcoreopsin, also reported in Coreopsis tinctoria (Yang et al, 2016). Peak 23d should correspond to a coreopsin derivative, although no definite identity could be assigned to it.…”
Section: Tcsp Pires Et Almentioning
confidence: 99%
“…The main active components of the extracts include phenolic acids (chlorogenic acid, caffeic acid) and different flavonoids (flavanomarein, marein, and okanin aurone) 18 . Flavanomarein and marein contents are generally the highest in Coreopsis tinctoria Nutt extracts, and may play a key role in quality assessment 19 . Previous experiments by our group showed that FM was absorbed into the blood as a prototype 20 .…”
Section: Flavanomarein (Fm) Is a Major Natural Compound Of Coreopsis mentioning
confidence: 99%
“…Most flavonoids or phenols showed an absorption maximum at around 240-290 or 300-350 nm. However, those phenolic compounds were mostly been detected at a UV wavelength of 280 nm (Seal 2016;Yang et al 2016), so the UPLC-based detection of the phenolic components in EEP samples was done at a wavelength of 280 nm in this study. As shown in Fig.…”
Section: Quantitation Of Ten Phenolic Components In Various Eep Samplmentioning
confidence: 99%